Vocabulary Differences - Muslih Ahmad Shikib (Peerian Journals Publishing, 2024)
There are some words that exist in American English and British English, but they differ in meaning and usage. An American geezer means (elderly person), but this word means (a person of any age, typically male, who might be one’s buddy or a person one thinks is ‘cool’) in British. Another example is an American house homely means (plain or ugly), on contrary, in the British Version, this word has (cozy, comfortable) meaning.
Keywords: homely; version; buddy